Association Between Visceral Adiposity Index and Insulin Resistance: A Cross-Sectional Study Based on US Adults - Jiang, Kai; Luan, Hong; Pu, Xiaolu; Wang, Mingxiang; Yin, Jiahui; Gong, Rongpeng (Frontiers in Endocrinology, 2022)
Abstract : Background: Visceral obesity index (Vai) is an empirical mathematical model used to evaluate the distribution and function of fat. Some studies have shown that Vai may be associated with the development of insulin resistance. In view of the differences in insulin resistance among different ethnic groups, this study attempts to analyze the special relationship between Vai and insulin resistance in American adults. Methods: We conducted a cross-sectional study through NHANES database. A total of 27309 patients over the age of 18 from the United States took part in the survey. It was divided into two groups: the IR-positive group and the IR-negative group. The association of VAI with IR was evaluated by logistic regression analyses mainly, including univariate analysis, multivariate regression analysis, curve fitting analysis and subgroup analysis. Results: The results showed that in the full-adjusted model, there is a strong positive association between VAI level and insulin resistance(OR: 1.28 (1.2~1.37), P<0.001) and there is a threshold effect. Conclusions: This study suggests that higher VAI levels are associated with insulin resistance. VAI index may be used as a predictor of insulin resistance. Keywords: Cross-sectional study; American adult; VAI; IR; NHANES